All Days 2005
DOI: 10.2118/93062-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Asphaltene-Induced Formation Damage

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractApplication of many EOR technologies provokes productivity decline due to asphaltene deposition leading to wellbore plugging and flow restriction in tubing, flow lines and production facilities. The present study aims at investigating the kinetics of asphaltene deposition using both model system and actual crude oil. Experiments were performed by injecting asphaltenic fluids into capillaries and outcrop sandstones. The effect of flow rate, presence of resins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…These include, first, a model system that consisted in Safania asphaltene dissolved in toluene and capillaries and more representative systems that consisted in three different crude oils (Weyburn, Hassi Messaoud and Arabian light) and Fontainebleau sandstones. Regarding model system and Weyburn crude oil, it was concluded that [15]: -Asphaltene deposition kinetics, indeed obeys the scaling law of the colloidal approach. -In the asphaltene deposition process, two main deposition regimes have been distinguished: -At low shear rate, and up to a first critical value (lower critical shear rate: γ cl ), the deposition is mainly diffusion-controlled and obeys the classical s = 2/3 power law (Equation 3 above) of the Diffusion Limited Deposition regime.…”
Section: Brief On the Previous Validation Workmentioning
confidence: 91%
See 3 more Smart Citations
“…These include, first, a model system that consisted in Safania asphaltene dissolved in toluene and capillaries and more representative systems that consisted in three different crude oils (Weyburn, Hassi Messaoud and Arabian light) and Fontainebleau sandstones. Regarding model system and Weyburn crude oil, it was concluded that [15]: -Asphaltene deposition kinetics, indeed obeys the scaling law of the colloidal approach. -In the asphaltene deposition process, two main deposition regimes have been distinguished: -At low shear rate, and up to a first critical value (lower critical shear rate: γ cl ), the deposition is mainly diffusion-controlled and obeys the classical s = 2/3 power law (Equation 3 above) of the Diffusion Limited Deposition regime.…”
Section: Brief On the Previous Validation Workmentioning
confidence: 91%
“…Moreover, it was clearly demonstrated that this shear rate limitation results from a dynamic equilibrium between hydrodynamic and adhesion forces. Recently [15,18], a systematic and thorough experimental investigation of the asphaltene deposition kinetics has been performed using different systems and under different experimental conditions. These include, first, a model system that consisted in Safania asphaltene dissolved in toluene and capillaries and more representative systems that consisted in three different crude oils (Weyburn, Hassi Messaoud and Arabian light) and Fontainebleau sandstones.…”
Section: Brief On the Previous Validation Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Asphaltenes can deposit both in the producing slots and in the formation face. Deposition of asphaltene precipitates over pore surface and/or across pore throats may reduce the effective pore space and/or severely impair the ability of oil to flow through porous formation, altering the rock wettability from water-wet to oil -wet, and increasing hydrocarbon viscosity by nucleating water-in-oil emulsions [1][2][3][4][5] . On the other hand, enhanced oil recovery (EOR) processes have become increasingly important to the petroleum industry.…”
Section: Introductionmentioning
confidence: 99%